One million cyclable blue/colourless electrochromic device using K2Zn3[Fe(CN)6]2 nanoparticles synthesized with a micromixer. Issue 70 (12th December 2019) - Takahashi, Akira; Noda, Keiko; Watanabe, Hiroshi; Kawamoto, Tohru
Abstract : Well-defined K2 Zn3 [Fe(CN)6 ]2 -nanoparticles (NPs) synthesized with a micromixer showed robust redox reaction cyclability. Abstract : Well-defined K2 Zn3 [Fe(CN)6 ]2 -nanoparticles (NPs) synthesized with a micromixer showed robust redox reaction cyclability. Crystal structure analysis revealed that the robustness results from the maintenance of the original rhombohedral crystal structure in the oxidation state. The blue/colourless electrochromic device with the K2 Zn3 [Fe(CN)6 ]2 -NPs and Prussian blue NPs showed recyclability over 1 million redox reactions.